Management of local multi-sensors applied to SHM and long-term infrared monitoring: Cloud2IR implementation. Issue 1 (2nd January 2019) - Crinière, Antoine; Dumoulin, Jean; Mevel, Laurent
ABSTRACT: Cloud2IR is an autonomous software architecture, allowing multi-sensor connection, dedicated to the long-term thermal monitoring of infrastructures. It has benefited of past experimental knowledge acquired in various research projects to redefine a lighter architecture using generic standards, more appropriated to autonomous operations in the field, and that can be later included in a wide distributed architecture. The system has been developed in order to cut down software integration time facilitating the system adaptation to each experiment specificities. After a detailed presentation of data standards, our bi-headed architecture is presented. First, a generic unit, a data management side able to aggregate any sensor data, type or size, automatically encapsulating them in various generic data format such as hierarchical data format or cloud data such as opengis standard. This whole part is also in charge of the acquisition scenario, the local storage management and the network management. Second, a specialised unit where the sensor specific development fitted to experimental requirements are addressed. The system has been deployed on two test sites for more than one year. It aggregates various sensor data issued from infrared thermal cameras, GPS units, pyranometers, weather stations, etc. The software and some results in outdoor conditions are discussed.